Musik dan Menyanyi Perspektif Fiqih Kontemporer - Maghudi, Muhammad Imam; M, Misbahadduin; Shuhufi, Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Singing accompanied by instruments (music) or without music is an issue that has always been debated among scholars since ancient times. They agree on some things and disagree on some things. There is disagreement or differences of opinion among scholars regarding the laws of music and singing. This is actually a problem ijtihâdiyah, namely problems in the realm ijtihad (fî majâl al-ijtihâd), in the sense of no jum?d (rigid), but wide open to interpretation (interpretation). This is because there are no texts that specifically qath'i (definitely) andshare (obviously) which prohibits music and singing. This type of research is library research (library research). The data sources used are primary and secondary data sources.